PENGEMBANGAN VIDEO BERCERITA MELALUI TEKNIK VENTRILOQUEST BERBANTUAN BONEKA TANGAN DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS II SD - Resa Zanuaristi, Alfariqa; Dwi Agus Setiawan; Denna Delawanti Chrisyarani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speaking skills play an important role in shaping students' communication skills from an early age because they affect self-confidence and the ability to express ideas. However, observations show that elementary school students' speaking skills are still low. This is due to learning that does not make sufficient use of technology and the use of media that is not interactive, so that students easily get bored and lack focus. This study aims to determine the validity, practicality, and effectiveness of storytelling videos using ventriloquist techniques with hand puppets in Indonesian language learning for second-grade elementary school students. Ventriloquism is the art of speaking without moving the lips, combined with hand puppets, so that the voice seems to come from the puppet. The puppet used is named Lala, a cheerful character who delivers educational messages interactively through a video titled “Painting is My Soul.” This study is a research and development study using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques include questionnaires, tests, expert validation sheets, and teacher and student response questionnaires. Data analysis was conducted qualitatively and quantitatively. The validation results showed that the media obtained a percentage of 91.66% from media experts, 92.85% from material experts, and 100% from language experts with an average of 94.83% categorized as very feasible. The practicality test showed that the media was very feasible.